2001
DOI: 10.2307/3090173
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Work and Well-Being

Abstract: Using two waves of panel data from Americans' Changing Lives (House 1995

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
873
9
35

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,260 publications
(997 citation statements)
references
References 43 publications
51
873
9
35
Order By: Relevance
“…Another study found a one-item measure of happiness correlated with a player's cricket batting average, which could be regarded as a behavioral outcome (Thoits & Hewitt, 2001). Overall, very little research can be found that examines the relationship between hedonic well-being and directly observed behaviors.…”
Section: Behavioral Correlatesmentioning
confidence: 99%
“…Another study found a one-item measure of happiness correlated with a player's cricket batting average, which could be regarded as a behavioral outcome (Thoits & Hewitt, 2001). Overall, very little research can be found that examines the relationship between hedonic well-being and directly observed behaviors.…”
Section: Behavioral Correlatesmentioning
confidence: 99%
“…Of course, being part of a romantic couple or social network involves many reciprocal exchanges, but fewer studies have analyzed how well-being is affected if the exchange is primarily about giving rather than receiving, such as using one's time to help others or engaging in voluntary organizations. Virtually all studies on the effects of volunteering on well-being find that people who engage in unpaid work to help others benefit in some way (e.g., Meier & Stutzer, 2008;Musick & Wilson, 2003;Piliavin, 2003;Thoits & Hewitt, 2001). For a brief overview of the recent research on volunteering and subjective well-being see Dolan, Peasgood & White (2008, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Although volunteering is believed to have beneficial effects for individuals, the relationship between volunteering and psychological well-being has received surprisingly little attention (Thoits and Hewitt 2001). There is a small body of evidence documenting the mental health benefits of volunteering for older adults (over 65), for whom volunteering has been shown to protect against depression (Musick and Wilson 2003).…”
Section: Introductionmentioning
confidence: 99%